Langmuir-Blodgett films : an introduction - Petty, Michael C. (Cambridge University Press, 1996)
This book provides a multidisciplinary introduction to the subject of Langmuir-Blodgett films. These films are the focus of intense current worldwide interest, as the ability to deposit organic films of nanometre thicknesses has many implications in materials science, and in the development of new electronic and opto-electronic devices. Beginning with the application of simple thermodynamics to the common bulk phases of matter, the book outlines the nature of the phases associated with floating monolayer films. The Langmuir-Blodgett deposition process itself is described in some detail and contrasted with other thin film techniques. Monolayer-forming materials and the structural, electrical and optical properties of Langmuir-Blodgett films are discussed separately. Each chapter is comprehensive, easy to understand and generously illustrated. Appendices are provided for the reader wishing to delve deeper into the physics and chemistry background.